Dimitros E. Psarros. Το Αϊβαλί και η Μικρασιατική Αιολίδα [Ayvalik and Aiolis of Asia Minor]. pp. 627, with b/w and col. ills, 1 map in bag pocket. 2017. Athens: Cultural Foundation of the National Bank of Greece (MIET). ISBN 978-960-250-687-5 - Karambinis, Michalis (Journal of Greek Archaeology, 2020)
This is a particular book, written by a refugee of second generation from Aivalik, who dedicated his life to the history of his homeland (he has studied Aivalik from 1969 till his death in 2008). An electrical engineer and architect by profession, a ‘‘technician’ and not an academic or a professional writer’, as Psarros himself states (579), the author prepared a book free of the scientific constraints that sometimes academic writings possess. Although his focus was on topography, settlement evolution and architecture, the author was not afraid to enter into the field of history, and the information he includes from his numerous oral interviews enlivens the places the author describes. In fact, reading, or better, wandering through the book, one has the feeling that he meets Fotis Kontoglou’s ‘heroes’ of his Το Αϊβαλί η πατρίδα μου (Athens 1962).